2019
DOI: 10.1002/qre.2491
|View full text |Cite
|
Sign up to set email alerts
|

An overview of synthetic‐type control charts: Techniques and methodology

Abstract: In this paper, we provide an overview of a class of control charts called the synthetic charts. Synthetic charts are a combination of a traditional chart (such as a Shewhart, CUSUM, or EWMA chart) and a conforming run‐length (CRL) chart. These charts have been considered in order to maintain the simplicity and improve the performance of small and medium‐sized shift detection of the traditional Shewhart charts. We distinguish between different types of synthetic‐type charts currently available in the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 96 publications
0
31
0
Order By: Relevance
“…Moreover, similar to Noorossana et al (2015), the proposed VSSI design can be combined with the improved double sampling design proposed in Malela-Majika et al (2019) to monitor the mean under the combined effect of autocorrelation and measurement errors. To further improve the detection ability of the process mean under the combined effect of autocorrelation and measurement errors, a number of adaptive synthetic schemes (see Rakitzis et al, 2019) based on the proposed VSSI design can be constructed. Also, when the underlying distribution departs from normality, the properties of the proposed scheme need to be re-investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, similar to Noorossana et al (2015), the proposed VSSI design can be combined with the improved double sampling design proposed in Malela-Majika et al (2019) to monitor the mean under the combined effect of autocorrelation and measurement errors. To further improve the detection ability of the process mean under the combined effect of autocorrelation and measurement errors, a number of adaptive synthetic schemes (see Rakitzis et al, 2019) based on the proposed VSSI design can be constructed. Also, when the underlying distribution departs from normality, the properties of the proposed scheme need to be re-investigated.…”
Section: Resultsmentioning
confidence: 99%
“…A number of authors have shown that if a monitoring scheme is designed based on one specific shift size δ , it would perform poorly when it is considerably different from the assumed one; see Reynolds and Lou and Ryu et al This makes the ARL inefficient in assessing the overall performance of a monitoring scheme. Thus, in addition to specific shift measures, ie, Equations and , researchers are encouraged to use some overall performance metric, like the expected ARL ( EARL ) because users tend not to know beforehand what exact shift value(s) is targeted—see, for example, Machado and Costa, Huh, (chapter 4) Tran et al, Malela‐Majika and Rapoo, You, Shongwe and Graham, and Rakitzis et al The EARL measures the performance of a monitoring scheme over a range of shift values, ie, δ min to δ max —which are the lower and the upper bound of δ , respectively. Note that the shifts within the interval [ δ min , δ max ] usually occur according to a probability density function (p.d.f.)…”
Section: Run‐length Properties Of the Rr W‐of‐w S‐and‐m Monitoring Schemementioning
confidence: 99%
“…It is observed that, in zero state, synthetic control chart performs better than X chart. Rakitzis et al 14 developed synthetic-type control chart. They proposed two types of synthetic control charts, namely, simple synthetic chart and improved synthetic chart.…”
Section: Synthetic Control Chartmentioning
confidence: 99%